Metabolic adaptations in skeletal muscle after 84 days of bed rest with and without concurrent flywheel resistance exercise - Irimia, José M; Guerrero, Mario; Rodriguez-Miguelez, Paula; Cadefau, Joan A; Tesch, Per A; Cussó, Roser; Fernandez-Gonzalo, Rodrigo (Journal of applied physiology (1985), 2017)
As metabolic changes in human skeletal muscle after long-term (simulated) spaceflight are not well understood, this study examined the effects of long-term microgravity, with and without concurrent resistance exercise, on skeletal muscle oxidative and glycolytic capacity. Twenty-one men were subjected to 84 days head-down tilt bed rest with (BRE; n = 9) or without (BR; n = 12) concurrent flywheel resistance exercise. Activity and gene expression of glycogen synthase, glycogen phosphorylase (GPh), hexokinase, phosphofructokinase-1 (PFK-1), and citrate synthase (CS), as well as gene expression of succinate dehydrogenase (SDH), vascular endothelial growth factor (VEFG), peroxisome proliferator-activated receptor gamma coactivator-1 (PGC-1α), and myostatin, were analyzed in samples from m. vastus lateralis collected before and after bed rest. Activity and gene expression of enzymes controlling oxidative metabolism (CS, SDH) decreased in BR but were partially maintained in BRE. Activity of enzymes regulating anaerobic glycolysis (GPh, PFK-1) was unchanged in BR. Resistance exercise increased the activity of GPh. PGC-1α and VEGF expression decreased in both BR and BRE. Myostatin increased in BR but decreased in BRE after bed rest. The analyses of these unique samples indicate that long-term microgravity induces marked alterations in the oxidative, but not the glycolytic, energy system. The proposed flywheel resistance exercise was effective in counteracting some of the metabolic alterations triggered by 84-day bed rest. Given the disparity between gene expression vs. enzyme activity in several key metabolic markers, posttranscriptional mechanisms should be explored to fully evaluate metabolic adaptations to long-term microgravity with/without exercise countermeasures in human skeletal muscle.